Food intake and consumption of dietary supplements by athletes of athletics modalities - Vanucci , Daniel Malta; Santos , Mateus Cezar dos; Oliveira, Thaina; Miller, Tânia Corrêa (Seven Editora, 2023)
The study aimed to identify the consumption of dietary supplements among athletes of different athletics modalities, to evaluate whether the dietary consumption of macronutrients meet the nutritional recommendations. The sample was composed of 30 athletes from different athletics modalities, focusing on competitive activity. To characterize the study group, the following data were collected: age, sex, weight and height. To know the food intake, the 24-hour Food Recall in triplicate was used, and the collection was performed on two non-consecutive days of the week and one day of the weekend. To quantify the macronutrients ingested by the athletes, the Dietbox software was used. Data analysis was descriptive with the support of the BioEstat 5.0 program. Participated in the research 30 athletes of both sexes, with a mean age of 16.5 ± 4.41 years, who had an average weight of 60.43 ± 22.81 kg. From the analysis of the 24-hour recalls, it was observed that 17% of the athletes used dietary supplements, of this total, 40% used supplements of protein origin, and these supplements were ingested on their own (40%) prescribed by a nutritionist (20%), physician (20%) or physical education professional (20%). In addition, it was also observed that 67% of respondents had a hypoglycidic diet, 73% of participants consumed a high-protein diet and 43% a high-fat diet. It is concluded that the consumption of macronutrients is not adequate for the sports modality, with the exception of the protein that is adequate for the modality practiced, being necessary strategies of nutritional education for athletes, with approaches on healthy and adequate eating, as well as on the consumption of food supplement, and this should be indicated after evaluation of the real need,  both performed by the professional nutritionist. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-146